Strategy for implementation of School child immunization month program In covid-19 pandemic at batujajar health center - Quintina Indriyana, Sri; Linasari, Desy; Masruroh, Enung (ACTA Medical Health Sciences, 2023)
The COVID-19 pandemic has hindered one of the government’s health sector programs, the School Child Immunization Month (BIAS). The complete immunization program must still follow the schedule to protect children from immunization-preventable diseases. This study sought strategies, processes, and obstacles in implementing the BIAS program during the COVID-19 pandemic at Batujajar Health Center from December 2020 to January 2021. The study design was a qualitative method by conducting in-depth interviews. The informants were selected through a purposive sampling technique to obtain the information required for the study. The results showed that immunization was only administered in safe zones, and socialization was distributed from the Community Health Centre to schools by WhatsApp (WA) application. The school used WA to deliver the socialization to parents, then recorded the students to immunize, and chose places fulfilling health protocols. The BIAS process during the COVID-19 pandemic was the selection of place, time, and the number of people involved for BIAS with the health protocol, monitoring by the immunization program coordinator through field officers reporting, and evaluations during monthly workshops. Some problems occurring in the BIAS program were there were external obstacles like school’s difficulty applying health protocols during the administration, and some parents’ resistance to children’s immunization, misinformation that it was a vaccine for COVID-19 or the vaccine was expired, children were sick of afraid of the syringe. Better socialization and coordination on the implementation of this program was needed DOI : 10.35990/amhs.v2n1.p9-20 REFERENCE Soedjatmiko, Sitaresmi, M. N., Rezeki, S., Hadinegoro, S., dkk. (2020). Jadwal Imunisasi Anak Umur 0–18 Tahun: Rekomendasi Ikatan Dokter Anak Indonesia Tahun 2020. Satuan Tugas Imunisasi IDAI. Sari Pediatri, 22(4), 252–260. Kementerian Pendidikan dan Kebudayaan Republik Indonesia. (2020). Surat Edaran Nomor 15 Tahun 2020 tentang Pedoman Penyelenggaraan Belajar dari Rumah dalam Masa Darurat Penyebaran COVID-19. Indriyana, S. Q., et al. (2020). Panduan Penyelenggaraan Pembelajaran pada Tahun Ajaran 2020/2021 dan Tahun Akademik 2020/2021 di Masa Pandemi COVID-19. Kemendikbud RI. Direktorat Surveilans dan Karantina Kesehatan, Kementerian Kesehatan RI. (2020). Petunjuk Teknis Pelayanan Imunisasi pada Masa Pandemi COVID-19. Jakarta. (2020). Imunisasi Selama Pandemi COVID-19. United Nations Children’s Fund. Kementerian Kesehatan RI. (2019). Profil Kesehatan Indonesia 2019. Jakarta: Kemenkes RI. Kementerian Kesehatan RI. (2017). Pedoman Pencegahan dan Pengendalian Difteri. Jakarta: Kemenkes RI. Puskesmas Batujajar. (2019). Penilaian Kinerja Puskesmas di Wilayah Kerja Puskesmas Batujajar Tahun 2019. Puskesmas Batujajar. (2020). Penilaian Kinerja Puskesmas di Wilayah Kerja Puskesmas Batujajar Tahun 2020. Irawati, N. (2020). Imunisasi Dasar dalam Masa Pandemi COVID-19. Jurnal Kesehatan Unila, Lampung. Ikatan Dokter Anak Indonesia (IDAI). (2020). Childhood Immunization Recommendations in COVID-19 Pandemic. Tersedia di: https://www.idai.or.id/about-idai/idai-statement/childhood-immunizationrecommendations-in-covid-19-pandemic Kementerian Kesehatan RI & UNICEF Indonesia. (2020). Imunisasi Rutin Anak Selama Pandemi COVID-19 di Indonesia: Persepsi Orang Tua dan Pengasuh. Triana, V. (2015). Faktor yang Berhubungan dengan Pemberian Imunisasi Dasar Lengkap pada Bayi. Jurnal Kesehatan Masyarakat Andalas, Padang. Direktorat Jenderal Pencegahan dan Pengendalian Penyakit, Kemenkes RI. (2018). Petunjuk Teknis Pelaksanaan Bulan Imunisasi Anak Sekolah (BIAS). Jakarta. Kementerian Kesehatan RI. (2017). Peraturan Menteri Kesehatan Republik Indonesia Nomor 12 Tahun 2017 tentang Penyelenggaraan Imunisasi. Jakarta: Kemenkes RI. Kementerian Kesehatan RI. (2014). Buku Ajar Imunisasi. Jakarta: Kemenkes RI. Sukmana, C., & Permatasari, V. R. (2021). Evaluasi Pelaksanaan dan Cakupan Program Imunisasi di Posyandu Lingkungan Rancapetir Ciamis. Indonesian Journal of Adult and Community Education, 3(2), Desember. Weiss, W. M., Winch, P. J., & Burnham, G. (2009). Factors Associated with Missed Vaccination during Mass Immunization Campaigns. Journal of Health, Population and Nutrition, 27(3), 358–367. Mkopi, A., Mtenga, S., Festo, C., Mhalu, G., Shabani, J., Tilly, R., et al. (2021). Vaccine, 39(41), 6041–6049. McKee, C., & Bohannon, K. (2016). The Journal of Pediatric Pharmacology and Therapeutics, 21(2), 104–109. Solida, A. (2016). Peran Orang Tua dalam Pemberian Imunisasi Campak pada Anak di Sekolah Dasar Luar Biasa Jambi Tahun 2015. Scientia Journal, 5(02), Desember.